1994
DOI: 10.1111/j.1467-8624.1994.tb00829.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Temperament and Mothering on Attachment and Exploration: An Experimental Manipulation of Sensitive Responsiveness among Lower‐Class Mothers with Irritable Infants

Abstract: infants selected on irritability shortly after birth and their mothers were randomly assigned to 2 intervention and 2 control groups to test the hypothesis that enhancing maternal sensitive responsiveness will improve quality of mother-infant interaction, infant exploration, and attachment. The intervention lasted 3 months and ended when the child was 9 months of age. When infants were 9 months of age, intervention group mothers were significantly more responsive, stimulating, visually attentive, and controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(58 citation statements)
references
References 63 publications
1
52
0
5
Order By: Relevance
“…A maioria dos pesquisadores da área concorda com a noção de que o temperamento tem bases biológicas ou constitucionais e se expressa logo após o nascimento. No entanto, há inúmeras evidências de que, assim como outras características do comportamento humano, o temperamento também sofre ação do ambiente, podendo ser por ele modificado (Boom, 1994;Bosa & Piccinini, 1994;Crockenberg & Smith, 2002;Wachs, 2002). Thomas e Chess (1977), pioneiros no estudo do temperamento, propuseram nove dimensões para sua definição: nível de atividade física, ritmo, reação da criança a novas situações, adaptabilidade, intensidade da reação emocional, atenção-persistência, limiar de resposta, distratibilidade e humor.…”
Section: Temperamento Infantil E O Desenvolvimento Socialunclassified
See 2 more Smart Citations
“…A maioria dos pesquisadores da área concorda com a noção de que o temperamento tem bases biológicas ou constitucionais e se expressa logo após o nascimento. No entanto, há inúmeras evidências de que, assim como outras características do comportamento humano, o temperamento também sofre ação do ambiente, podendo ser por ele modificado (Boom, 1994;Bosa & Piccinini, 1994;Crockenberg & Smith, 2002;Wachs, 2002). Thomas e Chess (1977), pioneiros no estudo do temperamento, propuseram nove dimensões para sua definição: nível de atividade física, ritmo, reação da criança a novas situações, adaptabilidade, intensidade da reação emocional, atenção-persistência, limiar de resposta, distratibilidade e humor.…”
Section: Temperamento Infantil E O Desenvolvimento Socialunclassified
“…1989;Boom, 1994). Essa característica da mãe favoreceria a ocorrência de interações sincrônicas e mutuamente recompensadoras entre a díade.…”
Section: Responsividade Materna E O Desenvolvimento Socialunclassified
See 1 more Smart Citation
“…Ainsworth's [1967] pioneering naturalistic observation work, conducted longitudinally across the infancy period, was designed to capture meaningful patterns of mother-infant interactive behavior in context rather than relying on frequency counts of discrete behaviors recorded without attention to the interactive environment in which they were embedded. Subsequent empirical efforts have revealed that transformations in the expression of attachment-related behavior are likely to emerge based on changes in the nature of dyadic processes such as maternal responsiveness and attention to infant interactive signals [Egeland and Farber, 1984;van den Boom, 1994]. Further, the attachment construct apparently has superior predictive validity related to a wide range of child outcomes when conceptualized as an organized system rather than as discrete units of behavior [Main et al, 1985;Sroufe and Waters, 1977].…”
Section: Conceptualization Of Attachment As a Dynamic Systemmentioning
confidence: 99%
“…The expanding body of research linking maternal sensitivity to attachment is predominantly correlational in nature, and with a few exceptions [e.g., van den Boom, 1994], several recent intervention studies have failed to effectively demonstrate a direct causal relationship of meaningful magnitude between the variables [van IJzendoorn, Juffer, and Duyvesteyn, 1995]. In an extensive descriptive and quantitative review of 16 preventive and therapeutic intervention studies designed to enhance parental sensitivity and ultimately infant attachment security, van IJzendoorn et al [1995] concluded that the majority of treatments implemented with parents of infants were effective in fostering improved parental sensitivity; yet, corresponding gains in attachment security were less frequently realized.…”
Section: Maternal Sensitivity and Attachment Qualitymentioning
confidence: 99%